2023
DOI: 10.1002/ar.25148
|View full text |Cite
|
Sign up to set email alerts
|

The effect of electroacupuncture at ST25 on Parkinson's disease constipation through regulation of autophagy in the enteric nervous system

Abstract: The effectiveness and safety of electroacupuncture (EA) for constipation have been confirmed by numerous clinical studies and experiments, and there are also studies on the efficacy of EA for Parkinson's disease (PD) motor symptoms. However, there are few researches on EA for PD constipation. Autophagy is thought to be involved in the mechanistic process of EA in the central nervous system (CNS) intervention in Parkinson's pathology. However, whether it has the same effect on the enteric nervous system (ENS) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…The efficacy of EA at ST25 on PD motor function and constipation symptoms was confirmed by a randomized controlled multicentre trial ( Li et al, 2023 ). In our previous study on the mechanism of EA at ST25 on PD constipation symptoms, its effects on motor symptoms were also observed ( Song et al, 2022 , 2023 ), and this paper further explored the therapeutic mechanism of motor symptoms on the basis of it. In the previous study, we also found that EA at ST25 changed the characteristics of gut microbiome in PD rats ( Song et al, 2023 ).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…The efficacy of EA at ST25 on PD motor function and constipation symptoms was confirmed by a randomized controlled multicentre trial ( Li et al, 2023 ). In our previous study on the mechanism of EA at ST25 on PD constipation symptoms, its effects on motor symptoms were also observed ( Song et al, 2022 , 2023 ), and this paper further explored the therapeutic mechanism of motor symptoms on the basis of it. In the previous study, we also found that EA at ST25 changed the characteristics of gut microbiome in PD rats ( Song et al, 2023 ).…”
Section: Introductionmentioning
confidence: 75%
“…In our previous study on the mechanism of EA at ST25 on PD constipation symptoms, its effects on motor symptoms were also observed ( Song et al, 2022 , 2023 ), and this paper further explored the therapeutic mechanism of motor symptoms on the basis of it. In the previous study, we also found that EA at ST25 changed the characteristics of gut microbiome in PD rats ( Song et al, 2023 ). According to the current cutting-edge research progress, the changes of gut microbiome are closely related to the onset and treatment of PD ( Travagli et al, 2020 ), which aroused our interest and prompted us to conduct related research.…”
Section: Introductionmentioning
confidence: 75%
“…[48] Electroacupuncture can promote the clearance of alpha-SYN and damaged mitochondria by regulating colonic autophagy, thereby restoring the Enteric Nervous System function and acting as an ameliorator of PD constipation. [49] Acupuncture can prevent intestinal microbiota from affecting the nervous system of PD mice by regulating and improving the diversity of intestinal microbiota, thus protecting substantia nigra neurons. [50] In addition, studies have shown that electroacupuncture improves stool excretion, accelerates intestinal propulsion, and improves intestinal motility in Thy1-αSYN mice.…”
Section: Ccsmentioning
confidence: 99%
“…Nevertheless, the authors also pointed out that the insufficient sample size and low data quality are the main limitations in this field. In addition, another TCM study involving the nervous system, specifically the potential mechanism of EA stimulating ST25 to improve constipation in Parkinson's disease, is also included in this issue (Song et al, 2023).…”
Section: Investigating the Potential Mechanism Of Tcm-based Therapy I...mentioning
confidence: 99%